Writing differently - Pullen, Alison; Helin, Jenny; Harding, Nancy (Dialogues in critical management studies ;, 2020)
Despite a substantial body of work arguing for a new form of writing about management, organisations, workers, ourselves, and our lives, these calls are ironically made within the traditional scientific language. This volume of Dialogues in Critical Management Studies makes an important effort to facilitate the growth of a nascent movement to write differently and thus capitalise on the fruitful and creative margins which this opens up. Writing Differently is a critical, insightful, poetic and timely collection of essays, poems, plays and auto-ethnographic pieces that showcases the potential of academic writing. These texts reflect how writing is not always something we control or have agency over, demonstrate the multiple ways of expressions that are possible when we write about that which matters and exhibit the rich and varied forms of writing that emerge in the processes of being involved in scholarly work. The volume will be of interest to those interested in alternative ways of working, researching, thinking, organizing, writing research and research lives.